PENGARUH KEPEMIMPINAN, KOMPENSASI, DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION KARYAWAN DI PERUSAHAAN KONTRAKTOR TAMBANG MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Muhammad Shohib; Kemal Farouq Mauladi; Mohammad Yaskun (J-MACC, 2024)
Human resources has the most important role for companies in various aspects, from policy makers to technical personnel for operational activities. The occurrence of turnover intention is the most important disruption factor in human resource management. An employee's decision to leave the job is influenced by many factors. This research aims to analyze the influence of leadership, compensation and organizational commitment on employee turnover intention at PT. Bangun Arta Hutama through job satisfaction as an intervening variable. The sample in this research was 123 BAMA employees in the operations and maintenance division. Data collection was carried out using a survey approach (digital questionnaire). The number of samples in this study was 123 employees. Test the research instrument using SPSS while testing the measurement model (Outer Model) and structural model (Inner Model) using SMART-PLS. The research results show that leadership has a significant negative effect on turnover intention. Compensation has a significant negative effect on turnover intention. Organizational commitment does not have a significant effect on turnover intention. Job satisfaction has a significant negative effect on turnover intention. Leadership and compensation can reduce turnover intention by increasing job satisfaction. Organizational commitment cannot reduce turnover intention through job satisfaction. This indicates that the increase in performance satisfaction and the desire of BAMA employees to change places of work is not influenced by organizational commitment.